Some reflections on the current global crisis from a developing countries perspective - Frenkel, Roberto (2009)
Frenkel and Rapetti contrast the genesis of the financial crisis in developed and developing countries and give an overview of policy repsonses so far. The authors offer policy options for financial regulations and counter cyclical policies as well as for the IMF. Above all, they argue for new policies and additional funds to enable governments in developing countries to push counter cyclical policies in order to reverse the crisis related economic downturn